A class of goodness‐of‐fit test for the additive hazards model with case‐cohort data. (10th December 2020) - Cao, Yongxiu; Yu, Jichang
Abstract: The case‐cohort design is commonly used in epidemiological studies due to its cost‐effectiveness. The additive hazards model is widely used in survival analysis when the hazards difference is constant. In this article, we propose a class of goodness‐of‐fit test statistics for the assumption of the additive hazards model with case‐cohort data through a class of asymptotically mean‐zero multiparameter stochastic processes. We also establish the asymptotic theory of the proposed test statistics and a resampling scheme is adopted to approximate its asymptotic distribution. The performance of the proposed test statistics is evaluated through simulation studies and a real dataset is analyzed to illustrate the proposed method.